Hubungan Kesepian dengan Gangguan Pola Tidur pada Lansia Hipertensi dan Tekanan Darah Normal di UPT PSTW Banyuwangi: The Relationship between Loneliness and Sleep Pattern Disorders in the Elderly with Hypertension and Normal Blood Pressure at UPT PSTW Banyuwangi - Insyaf Prawita Sari; Latifa Aini Susumaningrum; Penulis Hanny Rasni; Tantut Susanto; Diana Kholida (NERS Jurnal Keperawatan, 2022)
Loneliness affected sleep disorders among the elderly. A poor sleep pattern will be increasing blood pressure among elderly. The aimed his study was to analyzed the correlation between loneliness and sleep disorder among the elderly with hypertension. A case-control design was conducted among 51 elderlies (33 with hypertension, 18 with non-hypertension). A self-administered questionnaire was used to measure the sociodemographic of elderly while UCLA Loneliness Scale was used to measure loneliness, then the PSQI questionnaire was performed to measure sleep disorder. The correlation between loneliness and sleep disorder was analyzed using Chi-square test. The result showed among 51 elderly were 39,4% of mild loneliness of elderly with systole hypertension, and 75,8% of sleep disorder was mostly experienced by the elderly with systole hypertension. There were difference loneliness and sleep disorder among elderly with hypertension and non hypertension in systolic and diastoilc (p value<0,005). However, the level of loneliness (systole: x2= 10,143,p value=0,017; diastole: x2= 5,137,p value=0,162 ) and level of sleep disorder (systole: x2= 7,104,p value=0,008; diastole: x2= 0,391,p value=0,531) for hypertension of elderly were more higher compared with non hypertension of elderly. The conclusion of this study, there is a correlation between loneliness and sleep disorder among the elderly. Therefore, the elderly should more take part in activities in home nursing to express their feeling and reduce their loneliness.